NILAI-NILAI PERJUANGAN TOKOH UTAMA DALAM NOVEL HOME SWEET LOAN KARYA ALMIRA BASTARI - Trisnawati Zega; Dardanila; Emma Marsella (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Literary works, especially novels, reflect the values of life and can be a medium for reflecting social conditions. This research aims to describe the values of the main character's struggle in the novel Home Sweet Loan by Almira Bastari. This research uses a qualitative descriptive approach. The data and data sources of this research are in the form of words, quotations from the text contained in the novel Home Sweet Loan by Almira Bastari, fourth printing, 2023 published by Gramedia Pustaka Utama Publisher with a total of 312 pages. The data collection technique is done through literature study (read, listen, and note). Data analysis techniques include; identifying and processing data, reduction, and conclusion drawing based on Joyomartono's 1990 struggle value theory. The results of this study show five values of the main character's struggle, namely: (1) the value of sacrifice; (2) the value of patience; (3) the value of cooperation; (4) the value of never giving up, and (5) the value of respect. Based on the results of the study, the values of struggle in the novel Home Sweet Loan by Almira Bastari can provide a new understanding in analyzing the values of struggle in Indonesian literature with a different thematic context, provide a more specific focus, and a new perspective through different analysis for readers.